Artificial Intelligence in Sport: An Ethical Issue - DC, Suman (Unity Journal, 2022)
Sport technology is the tool designed and used by human beings to achieve sporting goals and values. Induction of technology in sports has revolutionized sport equipment, training materials, and biomedical technology, which have already posed a threat to the fairness in sport (Loland, 2018). Artificial intelligence (AI) refers to a technological system which is applied to process the external data to produce knowledge or facts about that data to fulfill specific goals and tasks in a short span of time (Haenlein & Kaplan, 2019). With the aim of fair operation of the game, administrators of modern-day sports have been adopting AI to officiate the game. However, the concept of technology is based on its instrumentality set by human beings, and ethical challenges of adopting AI in sports have greater impacts not only to the game itself but also to its participants (Loland, 2018; Watson, 2019), which itself remains a less explored area of study. To address this gap, this paper has investigated various umpiring technologies applied in modern-day cricket. For this, the study explores the concept of AI and the impacts of umpiring technology on game and stakeholders (players, officials/administrators, and other stakeholders such as broadcasters) through the lens of several cases. Methodologically, the study reviews the academic literature about the application of technology in sports, and qualitative data have been collected through the observation of a set of relevant cases displayed in live telecast of the recent games. Furthermore, official press releases of (inter) national sport governing bodies and their reactions presented by its stakeholders through the media have been analysed to explore the impacts in a wider community regarding umpiring technology. This paper concludes with the final observation and possible resolution of the ethical issues brought forth by umpiring technology in modern- day cricket. In the wider context, this research might help to reflect the ethical considerations of applying technology in global sports.